The pediatric gut bacteriome and virome in response to SARS-CoV-2 infection - Piazzesi, Antonia; Pane, Stefania; Del Chierico, Federica; Romani, Lorenza; Campana, Andrea; Palma, Paolo; Putignani, Lorenza (Frontiers in Cellular and Infection Microbiology, 2024)
Since the beginning of the SARS-CoV-2 pandemic in early 2020, it has been apparent that children were partially protected from both infection and the more severe forms of the disease. Many different mechanisms have been proposed to explain this phenomenon, including children's frequent exposure to other upper respiratory infections and vaccines, and which inflammatory cytokines they are more likely to produce in response to infection. Furthermore, given the presence of SARS-CoV-2 in the intestine and its ability to infect enterocytes, combined with the well described immunomodulatory capabilities of the microbiome, another potential contributing factor may be the presence of certain protective microbial members of the gut microbiota (GM).We performed shotgun metagenomic sequencing and profiled both the bacteriome and virome of the GM of pediatric SARS-CoV-2 patients compared to healthy, age-matched subjects. We found that, while pediatric patients do share some pro-inflammatory microbial signatures with adult patients, they also possess a distinct microbial signature of protective bacteria previously found to be negatively correlated with SARS-CoV-2 infectivity and COVID-19 severity. COVID-19 was also associated with higher fecal Cytomegalovirus load, and with shifts in the relative abundances of bacteriophages in the GM. Furthermore, we address how the preventative treatment of COVID-19 patients with antibiotics, a common practice especially in the early days of the pandemic, affected the bacteriome and virome, as well as the abundances of antimicrobial resistance and virulence genes in these patients. To our knowledge, this is the first study to address the bacteriome, virome, and resistome of pediatric patients in response to COVID-19 and to preventative antibiotics use.